Ruptured Jejunal Diverticulum Due to a Single-Band Small Bowel Obstruction - Rajaraman Durai; Ashish Sinha; Mihir Khan; Happy Hoque; Rajab Kerwat (The Scientific World Journal)
Jejunal diverticulosis is rare and often goes unnoticed until complications occur. The diverticula are true, acquired diverticula and often asymptomatic. Jejunal diverticulosis can be associated with diverticulosis of the duodenum, ileum, and colon. Here we describe a patient with known severe diverticular disease of the large bowel, who presented acutely with abdominal pain and signs of generalised peritonitis. Laparotomy showed ruptured jejunal diverticulosis with a single band over the terminal ileum, causing small bowel obstruction. Spontaneous perforation of a jejunal diverticulum is rare and is usually an intraoperative finding. One should exclude a precipitating cause, such as coexisting distal obstruction, stricture, or a foreign body.